A new species of Elcanidae (Insecta: Orthoptera) from mid-Cretaceous Kachin amber. (August 2022) - Zhou, Qian; Xu, Chunpeng; Jarzembowski, Edmund A.; Xiao, Chuantao
Abstract: A new species of Elcanidae (Orthoptera: Elcanoidea), Panorpidium maculosum sp. nov., is described based on an exquisite specimen with both wing and body preserved from mid-Cretaceous Kachin amber. Wing venation suggests attribution to Panorpidium mainly on developed ScP (with six branches), three longitudinal branches between basal part of RP and CuA + CuPaα, and area between MP and anal edge of tegmen narrow. Body morphologies exhibit similarity to Burmelcana including metatibia with pairs of spine-like spurs in distal half, metatibia with three apical spurs, and metabasitarsus with a row of stout spines on ventral margin. Thereby the combined characters of Panorpidium maculosum sp. nov., including body structures and wing venation, indicate that Burmelcana and Panorpidium belong to one genus and Burmelcana is junior homonym name of Panorpidium . Additionally, the new species distinguishes from the species of Panorpidium mainly by metathoracic basitarsus with a row of stout spines on distal half and area between MP and anal edge of tegmen narrow with oblique and netted crossveins, and is erected as a new species. Our new find not only confirms subfamilial assignation of Burmelcana to the Elcaninae, but also provides evidence for incorporating Burmelcana longirostris Peñalver and Grimaldi 2010 to Panorpidium .